Pelatihan Penerapan Good Manufacturing Practice Produk Sari Kedelai dan Bubuk Kedelai Pada IKM Usaha Berkat Doamu di Kota Payakumbuh - Nesti, Lisa; Meilizar, Meilizar; Jamsan, Firdaus; Musdirwan, Musdirwan; Elviana, Rahmi; Sutri, Reni (Journal of Industrial Community Empowerment, 2025)
Payakumbuh City is a key center for soybean production in West Sumatra, with an established industry focused on manufacturing and marketing health products, including soy milk and soy powder. At the IKM Usaha Berkat Doamu, however, a major issue has been identified: the soy milk spoils quickly, with a shelf life of only about 10 hours after processing, there is no standardized production and hygiene. As a result, around 50 packs of soy milk are damaged or stale each day, amounting to a loss of 13% of the total production (370 packs), causing significant daily financial losses for the business owner. This community service initiative aimed to address the problem by improving the packaging process and Good Manufacturing Process. The implementation method begins with the preparation stages of the activity, which include the target audience, location, work plan and schedule, delivery of materials and demonstrations, target partners, and planning for the evaluation of the community service activity implementation. The approach involved providing materials and conducting demonstrations on proper packaging and labeling techniques for soy milk. Led by instructors (lecturers), the activity included practical, hands- on training for the participants. As a result, the community gained valuable knowledge on packaging and labeling technologies, which will enhance the product’s marketability and competitiveness. The recommendation offered from this community service activity (PKM) is that future activities, in addition to implementing design of production facility layouts can be applied to support these food and beverage.